2002
DOI: 10.1128/jcm.40.1.84-88.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Amantadine-Resistant Influenza A Virus Strains in Nursing Homes by PCR-Restriction Fragment Length Polymorphism Analysis with Nasopharyngeal Swabs

Abstract: Annual consumption of amantadine increased abruptly after its approval for the treatment of influenza A virus infections in Japan in 1998, and the emergence of amantadine-resistant viruses is now a matter of concern. To detect resistant influenza A virus strains, we have developed a PCR-restriction fragment length polymorphism (PCR-RFLP) analysis for nasopharyngeal swabs. Three different primer sets for nested PCR were designed to incorporate restriction sites into the amplicon to differentiate single-amino-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
8

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 17 publications
(35 reference statements)
0
47
0
8
Order By: Relevance
“…The genetic basis for resistance to these drugs is associated with amino acid substitutions at positions 26, 27, 30, 31 or 34 in the transmembrane region of the M2 protein (Pinto et al 1992;Holsinger et al 1994). It was reported that roughly 1/3 of patients develops resistance after treatment (Hayden and Hay 1992;Saito et al 2002), but resistance in pre-treatment samples, or community prevalence, remained low in the past, as 0-3% in Japan (Suzuki et al 2001(Suzuki et al , 2003, and roughly 1% in the United States and the United Kingdom (Ziegler et al 1999;Tooley 2002). However, Bight and colleagues (Bright et al 2005(Bright et al , 2006 recently highlighted a dramatic increase in the prevalence of amantadine resistant H3N2 influenza strains in Asian countries and USA.…”
mentioning
confidence: 99%
“…The genetic basis for resistance to these drugs is associated with amino acid substitutions at positions 26, 27, 30, 31 or 34 in the transmembrane region of the M2 protein (Pinto et al 1992;Holsinger et al 1994). It was reported that roughly 1/3 of patients develops resistance after treatment (Hayden and Hay 1992;Saito et al 2002), but resistance in pre-treatment samples, or community prevalence, remained low in the past, as 0-3% in Japan (Suzuki et al 2001(Suzuki et al , 2003, and roughly 1% in the United States and the United Kingdom (Ziegler et al 1999;Tooley 2002). However, Bight and colleagues (Bright et al 2005(Bright et al , 2006 recently highlighted a dramatic increase in the prevalence of amantadine resistant H3N2 influenza strains in Asian countries and USA.…”
mentioning
confidence: 99%
“…Nucleic acid was extracted with the use of viral RNA kit (QIAamp, Qiagen ® , Valencia, CA ) and tested by reverse‐transcriptase‐polymerase‐chain reaction (RT‐PCR). Neuraminidase and matrix protein 2 genes were amplified by RT‐PCR with the following specific primers: bases 617–995 (338 pdb fragment) of the influenza A matrix protein 2, M2‐For3 (5′‐CTAGTCAGGCCAGGCAAATG‐3′) and M2‐Rev (5′‐ACTGTCGTCAGCATCCACAG‐3′); 21 bases 449–1218 (769 pdb fragment) of the influenza A neuraminidase 1, AN1A (5′‐AGGACAGAAGCCCTTATAGG‐3′) and AN1DII (5′‐TTAGCTCAGGATGTTGAACG ‐3′); bases 299–997 (698 pdb fragment) of the influenza A neuraminidase 2, AN2A (5′‐ATTACAGGATTTGCACCTTT‐3′) and H3N2‐NA‐2R (5′‐GGGTGTGTCTCCAACAAGTCTGAGCAC‐3′); bases 352–641 (289 pdb fragment) of the influenza B neuraminidase, NA‐RES‐F (5′‐GCTCTAACCCATTATGCAG‐3′) and NA‐RES‐R (5′‐CTTTCTTGTGTTCTTAGGATG‐3′).…”
Section: Methodsmentioning
confidence: 99%
“…Este fenómeno se ha observado principalmente en comunidades cerradas como son los asilos de ancianos e instituciones de salud [9][10] . Respecto a la frecuencia de adquisición de esta resistencia, distintos estudios muestran resultados muy variables: desde 10 a 30% en algunas series 6,9,11-13 a 1,5 y 3,4% en otras [10][11][12][13][14] . La generación de resistencia ocurre entre los 2 y 7 días de iniciado el tratamiento habiéndose documentado propagación de virus resistentes entre los contactos cercanos 6,13 .…”
Section: Introductionunclassified
“…La adquisición de resistencia se debe a mutaciones en los genes que codifican para los aminoácidos constituyentes del dominio transmembrana de la proteína M2. Estas mutaciones ocurren en las posiciones 26, 27, 30 y 31, siendo esta última la más frecuente ya que da cuenta de 70 a 80% de los casos 12 . La metodología tradicional para la detección de cepas resistentes en el laboratorio es compleja y consiste en demostrar la pérdida de la capacidad de inhibir cultivos celulares en presencia de amantadina 15 .…”
Section: Introductionunclassified
See 1 more Smart Citation